Bothrops pauloensis snake venom-derived Asp-49 and Lys-49 phospholipases A2 mediates acute kidney injury by oxidative stress and release of inflammatory cytokines. (30th January 2021) - Marinho, Aline Diogo; Silveira, João Alison de Moraes; Chaves Filho, Adriano José Maia; Jorge, Antônio Rafael Coelho; Nogueira Júnior, Francisco Assis; Pereira, Venúcia Bruna Magalhães; de Aquino, Pedro Everson Alexandre; Pereira, Cássia Arruda Souza; Evangelista, Janaina Serra Azul Monteiro; Macedo, Danielle Silveira; Lima Júnior, Roberto César Pereira; Toyama, Marcos Hikari; et al.
Abstract: The envenomation caused by the Bothrops pauloensis snake leads to severe local and systemic effects including acute kidney injury. In this study, we investigated the renal effects by phospholipases A2 (PLA2s), divided into two main subgroups, Asp-49 and Lys-49, isolated from the Bothrops pauloensis snake venom ( Bp V) in isolated rat kidney system. Both PLA2s (3 μg/mL), added alone to the perfusion system and analyzed for 120 min, had significant effects on isolated rat kidney. Asp-49 reduced Glomerular Filtration Rate (GFR) at 60, 90 and 120 min, and the percentage of total tubular sodium transport (%TNa + ) and potassium transport (%TK + ) at 120 min. Lys-49 increased Perfusion Pressure (PP) at 120 min and reduced GFR, %TNa + and the percentage of total tubular chloride transport (%TCl − ) at 60, 90 and 120 min. Cytokine release in the kidney tissues were increased with Asp-49 PLA2 (IL-10) and Lys-49 PLA2 (TNF-α, IL-1β, IL-10). Both increased MPO activity. Asp-49 PLA2 decreased Glutathione (GSH) and increased nitrite levels, while Lys-49 PLA2 increased Malondialdehyde (MDA), GSH and nitrite levels. Histological analysis of the perfused kidneys revealed the presence of glomerular degeneration and atrophy, deposit of proteinaceous material in Bowman's space and intratubular with both PLA2s. These findings indicated that both PLA2s modified the functional parameters in an isolated perfused kidney model with increased oxidative stress and cytokine release. PLA2s are one of the components at high concentration in Bp V and our results provide important knowledge about their involvement with the nephrotoxic mechanism. Highlights: Both Asp-49 and Lys-49 PLA2 fractions induced vascular and functional alterations in the isolated kidney system. The nephrotoxicity induced by both Asp-49 and Lys-49 PLA2 fractions involved oxidative stress. Asp-49 and Lys-49 PLA2 caused toxicity mediated by release of the inflammatory cytokines.